Ibrah and Tarbiyah: The Approaches to Learning and Teaching in Kuasa Kata dari Lisan Mengalir ke Lautan Aksara: (Wasilah Ibrah dan Tarbiah dalam Kuasa Kata dari Lisan Mengalir ke Lautan Aksara) (Malay Literature, 2015)
The relationship between teaching and educating is significant in the impression of life. It is not merely a subject in the school syllabus, or components extracted from the process of reading a literature text. In fact, these two elements, ibrah (learning) and tarbiyah (teaching) according to the Islamic perspective have a more extensive meaning in order to build a stronger society. It is found that these elements, ibrah and tarbiyah, form a strong bond in developing the core values of life and society. Thus, this article is an explanation on the approaches of ibrah and tarbiyah in the memoir by Mahaya Md. Yassin titled Kuasa Kata dari Lisan Mengalir ke Lautan Aksara. This article describes the significance of the approaches of ibrah and tarbiyah in the literary work mentioned, in which the relationship between human beings with one another (hablmin al-Nas) and the relationship of humans with The Creator (habl min Allah) are advocated. Based on this study, it is clear that the author includes four approaches of ibrah and tarbiyah in her writing, i.e. concerning family, career, work and leadership, to support her message. This study also shows that the memoir is a valuable form of information and a guide to learning and teaching for all concerned.Keywords: wasilah, ibrah and tarbiyah, literature text, memoir